2023
DOI: 10.1057/s41262-022-00307-4
|View full text |Cite
|
Sign up to set email alerts
|

Social media activism for resurrecting deleted brands: the role of consumers’ psychological reactance

Abstract: When companies delete brands, devoted, yet unhappy consumers experience psychological reactance and initiate brand resurrection movements (BRMs) to bring their beloved brand back into their lives. In this Web 2.0 era, numerous consumer-led activism initiatives have been launched via social media to resurrect dead brands. On the other hand, relaunching a deleted brand is a crucial decision for a company and involves various financial and strategic implications. Therefore, it becomes imperative for brand manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 85 publications
0
3
0
Order By: Relevance
“…A previous study on the advertisement on social media showed that only 13.02% of users found the advertisement on Instagram informative and useful, a percentage significantly lower when compared to Google (33.53%), Pinterest (29.72%), and Twitter (21.21%) [ 27 ]. The low user engagement of Instagram posts with advertisements might result from psychological reactance (an urge to resist the initial intention of the message) [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on the advertisement on social media showed that only 13.02% of users found the advertisement on Instagram informative and useful, a percentage significantly lower when compared to Google (33.53%), Pinterest (29.72%), and Twitter (21.21%) [ 27 ]. The low user engagement of Instagram posts with advertisements might result from psychological reactance (an urge to resist the initial intention of the message) [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…, 2022), the impact of social norms on consumer behavior (Melnyk et al. , 2022), revenge buying (Gupta and Mukherjee, 2022) and social media activism (Almazyad et al. , 2023).…”
Section: Theory Of Psychological Reactancementioning
confidence: 99%
“…The theory posits that such a behavioral outcome would result from reasserting one's freedom, the latter being defined "as a belief that one can engage in a particular behavior" (Brehm and Brehm, 1981, p. 35), whereby "behavior" subsumes any performable act such as (not) choosing an alternative, (not) having an opinion about a particular matter, or (not) doing something (Brehm, 1966). Reactance theory has been used widely in marketing and consumer research to study issues as diverse as framing of marketing communications (Loebnitz et al, 2022), the impact of social norms on consumer behavior (Melnyk et al, 2022), revenge buying (Gupta and Mukherjee, 2022) and social media activism (Almazyad et al, 2023).…”
Section: Theory Of Psychological Reactancementioning
confidence: 99%